Analisis Perubahan Penggunaan Lahan di Kecamatan Mijen Kota Semarang Tahun 2010 - 2014 - Williyantoro, Wahyu Aji; , Dr. Kuswaji Dwi Priyono, M. Si; , Ir. Taryono, M. Si (2016)
Mijen Subdistrict of Semarang District is an area of research conducted by the author. The purpose of this research is: (1) analyzing land use changes that occurred between 2010-2014, (2) analyze the factors affecting land use change, and(3) analyzing the fit between the direction of land use in 2010-2014 with the Regional Spatial Plan of Semarang. Mijen Subdistrict has 14 villages namely Karangmalang, Polaman, Tambangan, Cangkiran, Bubakan, Purwosari, Jatibarang, Jatisari, Mijen, Kedungpani, Pesantren, Wonoplumbon, Ngadirgo, Wonolopo. The research method used is secondary data analysis method Data analysis is done by computer using software techniues Arc Gis 10 through overlaying maps. The results of overlaying a map used to determine the land use changes that occured between 2010 and 2014. Secondary data analysis is used to determine the factors that influence land use change. Regional Spatial Plan of Semarang years 2011-2031 as a reference to determine the suitability of the direction of land use in 2010 and 2014 with the regional spatial plan of Semarang. The results of the study are as follows: 1) There has been a change in land use from agriculture to non-agriculture by 10,76 km2, 2) population growth, accessibility and facilities into the factors affecting land use changes. 3) the change is not appropriate because of many irregularities with the Regional Spatial Plan of Semarang.